Influence of previous exposure to human parvovirus B19 infection in explaining susceptibility to rheumatoid arthritis: an analysis of disease discordant twin pairs. Issue 2 (February 1994) - Hajeer, A H; MacGregor, A J; Rigby, A S; Ollier, W E; Carthy, D; Silman, A J
Abstract : OBJECTIVES–To assess the association between exposure to parvovirus B19 and susceptibility to rheumatoid arthritis (RA). METHODS–One hundred and fifty five twin pairs (76 monozygotic (MZ) and 79 dizygotic (DZ)), discordant for RA, were tested for the presence of IgG antiparvovirus antibodies using ELISA. The data obtained were analysed using conditional logistic regression, from which odds ratios and 95% confidence intervals were calculated. RESULTS–Overall, there was no association between exposure to parvovirus and RA (OR = 1.2, 95% CI: 0.7-1.7). However, in two subgroups there was a suggestion of an association. These were: (1) pairs where the affected twin was rheumatoid factor (RF) seronegative (OR = 2.0, 95% CI: 0.9-12.4) and (2) in opposite-sexed twin pairs where the affected twin was female (OR = 3.0, 95% CI: 0.9-11.6). CONCLUSION–Previous exposure to parvovirus infection did not explain disease susceptibility in both MZ and DZ discordant pairs with rheumatoid arthritis. This infection, however, might be relevant in some subgroups.